2018
DOI: 10.1002/cpe.4508
|View full text |Cite
|
Sign up to set email alerts
|

Chinese microblog rumor detection based on deep sequence context

Abstract: Summary Rumor is one of the main problems in social media, which often shows deeply and rapidly undesirable affection on the society. Although many rumor detection models consider content features and social features, all of them are based on the word independence assumption, which lacks the sequence context. Thus, if we use some words that often appear in rumors, our posts will be recognized as a rumor. To solve this problem, we propose a deep sequence context model (DSCM) for Chinese microblog rumor detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…e rumor detection module is used to extract features, and the checkpoint module is used to solve the problem of timeliness, which is used to trigger the rumor detection module to ensure the timeliness of rumor detection while ensuring accurate identification of rumors. Lin et al [15] raised the issue of word independence and found that some common words appear in rumors. Once these words appear, they can be judged as rumors.…”
Section: Related Workmentioning
confidence: 99%
“…e rumor detection module is used to extract features, and the checkpoint module is used to solve the problem of timeliness, which is used to trigger the rumor detection module to ensure the timeliness of rumor detection while ensuring accurate identification of rumors. Lin et al [15] raised the issue of word independence and found that some common words appear in rumors. Once these words appear, they can be judged as rumors.…”
Section: Related Workmentioning
confidence: 99%
“…A deep learning approach can learn from the simple inputs of contexts and changes in the content of hidden representations. For detecting rumors in Chinese microblogs, Lin et al 3 proposed a sequence model with RNNs, wherein falsity and influence were the two key factors in each rumor. To better understand a rumor, their model captured the bi‐directional sequence content.…”
Section: Related Workmentioning
confidence: 99%
“…However, the low concurrency of multilayer RNNs will lead to long execution time both in the training and testing phases. The popularity of deep learning has warranted the need for research 2,3 using RNNs, which has significantly reduced the efficiency of the models 2,3 . A lack of concurrency indicates that more time and resources are required during the training phase.…”
Section: Introductionmentioning
confidence: 99%
“…The first systematic and scientific study of rumors began in 1942, 1 and then with the constant change of rumor propagation platform and the development of computer technology, the research theory of rumor propagation has changed from the initial applied mathematical theory and applied physics theory to the current applied computer theory and complex network theory. With the rapid development of mobile social network platform, 2,3 the most valuable research theory is undoubtedly the latest complex network theory. However, in the current researches on rumor propagation based on complex networks, traditional complex network models, such as Barabási–Albert (BA) model and Watts–Strogatz (WS) model, are mostly used as experimental networks.…”
Section: Introductionmentioning
confidence: 99%